Addition of Talcum to the formulation of clindamycin capsule preparations on evaluation test results - Ivonder; Savira Sandriansyah (Strada Journal of Pharmacy, 2019)
Medicines are all single ingredients or mixtures that are used by all living creatures internally and externally, to prevent, alleviate or cure disease. In general, according to the dosage form, drugs are divided into 3 types, namely liquid preparations, semi-solid preparations and solid preparations. In this practicum we made a solid dosage form, namely capsules (Ansel, 1989). Capsules are solid preparations consisting of medication in a hard or soft shell that can dissolve (Fatmawaty et al, 2012). Hard capsules are usually made from gelatin which consists of the capsule shell, the body and the capsule cap. The two parts of the capsule cover will cover each other when brought together and the cover will cover the body of the capsule (Ansel, 2005). Clindamycin inhibits most gram-positive cocci and most anaerobic bacteria, but cannot inhibit aerobic gram-negative bacteria such as 33 Haemophilus, Mycoplasma and Chlamydia (Ministry of Health, 2011). The mechanism of action of clindamycin is the same as erythromycin. Clindamycin is mainly given to treat infections caused by anaerobic bacteria, such as Bacteriodes fragilis bacteria which often cause abdominal infections caused by trauma (Katzung, 2012). Considering the importance of knowledge about antibiotic drugs such as clindamycin, a good and correct method for formulating solid capsule dosage forms has been developed and what must be taken into account when making them. Based on the test results, F1 3.44 seconds, F2 3.76 seconds, F3 3.24 seconds, the flow speed of these three formulas meets the flow speed requirements, namely flow speed ≥ 10 g/second. The flow speed of the three formulas is in the good category, namely 2-10 g/sec which is said to be very good while it is said to be good. The flow speed is good because Aerosil has a very small and fine particle size. Apart from being an absorbent, aerosols are also able to improve flow properties by reducing friction between particles and by averaging test results from angles of repose F1 45°, F2 43° and F3 53°.